Scaling up HIV Treatment for MSM in Bangkok : What Does It Take? – A Modelling and Costing Study - Zhang, Lei; Phanuphak, Nittaya; Henderson, Klara; Nonenoy, Siriporn; Srikaew, Sasiwan; Shattock, Andrew J.; Kerr, Cliff C.; Omune, Brenda; van Griensven, Frits; Osornprasop, Sutayut; Oelrichs, Robert; Ananworanich, Jintanat; et al. (World Bank, Washington, DC, 2015)
The HIV epidemic amongst men who have sex with men (MSM) in Bangkok is substantial. The population size of MSM in Bangkok is 120,000-250,000, with approximately one-third (33.5 percent) considered high-risk, characterized by their young age, multiple partnerships, frequent unprotected anal intercourse, and sexual activities around MSM hotspots. In metropolitan Bangkok, HIV prevalence among MSM reportedly increased from 21 percent to 28 percent between 2000 and 2012. The Thai Working Group of Estimation and Projection (2013) projected an estimate of 39,000 new HIV infections would occur in Thailand during 2012-2016, based on the AIDS Epidemic Model (AEM). MSM will account for 44 percent of these new HIV cases, and 25-30 percent of these infections will likely to occur in Bangkok. In 2011, the United Nations held a high-level meeting on HIV/AIDS where they adopted the ambitious epidemiological targets of the United Nations Political Declaration on HIV/AIDS (UNPD), to be met by 2015. Attaining these specific targets would lead to substantial progress towards ending AIDS. UNAIDS has also been prioritizing the “Getting to Zero” initiative (“Zero new HIV infections. Zero AIDS-related deaths. Zero discrimination.”). The Bangkok Metropolitan Administration (BMA) recently responded with the “Bangkok: Getting to Zero” initiative, which strategizes an increased focus on prevention amongst MSM in the city. The clinical trial, HPTN052, demonstrated a 96 percent reduction of HIV transmission among heterosexual discordant couples who received ART. “Treatment as prevention” has become an increasingly accepted strategy to prevent new infections. A cost-effectiveness analysis comparing current levels of investment in targeted HIV prevention interventions for MSM in Bangkok (including treatment), with scenarios of increased coverage, would provide evidence to shape efficient national and metropolitan strategies. A return-on-investment analysis would provide an economic rationale to finance this strategy in allocating sufficient resources to address the epidemic at the most appropriate scale. Demonstration by the study that a significant reduction in transmission (including potential elimination) are both feasible and cost effective, may galvanize global political support.